Investment in Constructed Environment for Tourism Development - A S Sochipem Zimik; Arup Barman (PT FORMOSA CENDEKIA GLOBAL, 2023)
The study attempts to analyses the necessity for investment in the constructed environment and emphasizes the importance in covering all aspects of tourism industry development. Various ethical and regulatory issues are examined in detail in relation to the necessity for investment and acquiring confidence in tourist growth. Concerning the need for tourist development, the research seeks to convey the strong message that tourism sectors are heavily reliant on the constructed environment. We have addressed not only the element of tourism development demands, but also the role and duty shared by all players involved in the tourist industry. One of the study's important takeaways is the necessity for an open and healthy tourist market in order for investors to be invited and participate in the growth of tourism sectors by investing in the built environment